Optically Induced Phase Change for Magnetoresistance Modulation. Issue 3 (9th January 2020) - Wei, Guodong; Lin, Xiaoyang; Si, Zhizhong; Wang, Dong; Wang, Xinhe; Fan, Xiaofei; Deng, Kun; Liu, Kai; Jiang, Kaili; Lei, Na; Chen, Yanxue; Mangin, Stephane; et al.
Abstract: Optical methods for magnetism manipulation have been considered as a promising strategy for ultralow‐power and ultrahigh‐speed data storage and processing, which have become an emerging field of spintronics. However, a widely applicable and efficient method has rarely been demonstrated. Here, the strongly correlated electron material vanadium dioxide (VO2 ) is used to realize the optically induced phase change for control of the magnetism in NiFe. The NiFe/VO2 bilayer heterostructure features appreciable modulations of electrical conductivity (32%), coercivity (37.5%), and magnetic anisotropy (25%). Further analyses indicate that interfacial strain coupling plays a crucial role in the magnetic modulation. Utilizing this heterostructure, which can respond to both optical and magnetic stimuli, a phase change controlled anisotropic magnetoresistance (AMR) device is fabricated, and reconfigurable Boolean logics are implemented. As a demonstration of phase change spintronics, this work may pave the way for next‐generation opto‐electronics in the post‐Moore era. Abstract : Optical methods for magnetism manipulation have been considered as a promising strategy for ultralow‐power and ultrahigh‐speed electronic applications. The magnetoresistance modulation by optically induced phase change in NiFe/VO2 heterostructures is reported. The interfacial magneto‐elastic coupling may contribute to this appreciable modulation effect. The work, as an example of phase change spintronics, may trigger the development of innovative opto‐electronic devices.